SOCIO-ECONOMIC PROFILE OF DUCK FARMERS IN TAMIL NADU - I. Sharmila; N. Vimalraj Kumar; K. Devaki; P. Veeramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out in eight highly duck populated districts comprised of four clusters of Tamil Nadu. From each of the clusters, 40 duck farmers were selected randomly to study their socio-economic status. Using a pre-tested, structured schedule, data were collected through face to face interview method. The results of the study revealed that 50.60 per cent of the farmers belonged to old age group (Above 45 years). Most of the farmers were married (92.50 %) and majority of them were found to be illiterate (48.80 %). Most of the farmers found to be rearing ducks as their primary occupation (84.37 %). Highest proportion of farmers (43.75 %) had duck farming experience of 37 – 55 years. The risk-taking abilities of the duck farmers were at medium level (51.50 %). Nearly one-half (48.75 %) of the respondents had contact with input dealers followed by 33.75 per cent had contact with progressive farmers for obtaining information’s related to duck farming.